Cognitive Fusion Social Anxiety and Rejection Sensitivity in Young Adults with Visible Physical Disabilities - Sana Ameen; Javeria Zafar; Umara Sameer; Nazia Nisar (Research Journal of Psychology, 2025)
Young adults in Pakistan with visible physical disabilities often encounter psychological challenges, particularly in social interactions. This study examined the relationship between cognitive fusion, social anxiety, and rejection sensitivity within this population. Cognitive fusion involves a strong attachment to distressing thoughts, which may contribute to emotional and interpersonal difficulties. A cross-sectional design was employed and 149 participants aged 18 to 26 were recruited through purposive sampling from various rehabilitation centers and disability organizations in Lahore. Standardized instruments—the Cognitive Fusion Questionnaire (CFQ), Social Interaction Anxiety Scale (SIAS), and Adult Rejection Sensitivity Questionnaire (A-RSQ)—were used for assessment. Data were analyzed using Spearman rho correlation and bootstrapped linear regression through SPSS version 27. Results indicated a significant positive correlation between cognitive fusion and social anxiety, while no significant relationship was found with rejection sensitivity. These findings suggest that psychological interventions should be tailored to address identity-related cognitive patterns among youth with visible physical disabilities to promote mental well-being.